TAF4b and TAF4 differentially regulate mouse embryonic stem cells maintenance and proliferation. (27th January 2013) - Bahat, Anat; Kedmi, Ranit; Gazit, Kfir; Richardo‐Lax, Inna; Ainbinder, Elena; Dikstein, Rivka
<x xml:space="preserve">Abstract</x> TAF4b is a cell type‐specific subunit of the general transcription factor TFIID. Here, we show that TAF4b is highly expressed in embryonic stem cells (ESC) and is down‐regulated upon differentiation. To examine the role of TAF4b in ESC, we applied a knockdown (KD) approach. TAF4b depletion is associated with morphological changes and reduced expression of the self‐renewal marker alkaline phosphatase. In contrast, KD of TAF4, a ubiquitously expressed TAF4b paralog, retained and even stabilized ESC stemness. Retinoic acid‐induced differentiation was facilitated in the absence of TAF4b but was significantly delayed by TAF4 KD. Furthermore, TAF4b supports, whereas TAF4 inhibits, ESC proliferation and cell cycle progression. We identified a subset of TAF4b target genes preferentially expressed in ESC and controlling the cell cycle. Among them are the germ cell‐specific transcription factor Sohlh2 and the protein kinase Yes1, which was recently shown to regulate ESC self‐renewal. Interestingly, Sohlh2 and Yes1 are also targets of the pluripotency factor Oct4, and their regulation by Oct4 is TAF4b‐dependent. Consistent with that, TAF4b but not TAF4 interacts with Oct4. Our findings suggest that TAF4b cooperates with Oct4 to regulate a subset of genes in ESC, whereas TAF4 is required for later embryonic developmental stages.